Trends in screening breast magnetic resonance imaging use among US women, 2006 to 2016. Issue 24 (28th September 2020) - Wernli, Karen J.; Callaway, Katherine A.; Henderson, Louise M.; Kerlikowske, Karla; Lee, Janie M.; Ross‐Degnan, Dennis; Wallace, Jamie K.; Wharam, J. Frank; Zhang, Fang; Stout, Natasha K.
Abstract : Background: Supplemental breast cancer screening with breast magnetic resonance imaging (MRI) is recommended for women at high risk of breast cancer. To the authors' knowledge, recent national trends in breast MRI use are unknown. Methods: The authors used claims data from a large national insurer to calculate screening breast MRI rates from 2006 to 2016 in a US cohort of 10 million women aged 20 to 64 years. Use was stratified by subgroups of women with a BRCA mutation, family history of breast cancer, and prior breast cancer history and stratified by age. Joinpoint regression evaluated annual changes in trends. Results: The total sample included 37, 447 screening breast MRI examinations in 25, 617 women. Overall screening breast MRI rates were low and increased from 2.9 to 12.1 examinations per 10, 000 women from 2006 to 2016. MRI use in women with a BRCA mutation increased by 21% on average annually from 210.8 per 10, 000 women to 1562.0 per 10, 000 women from 2006 to 2016. By 2016, women aged 50 to 64 years who had a BRCA mutation had the highest use of breast MRI (1669.6 MRI examinations per 10, 000 women) compared with younger women (1198.4 MRI examinations per 10, 000 women, 1519.1 MRI examinations per 10, 000 women, and 1567.2 MRI examinations per 10, 000 women, respectively, among women aged 20‐29 years, 30‐39 years, and 40‐49 years). Women with a BRCA mutation comprised <1% of the current study population but received approximately 9% of screening breast MRI examinations. Breast MRI rates among women with a family history of breast cancer or prior breast cancer history initially increased from 2006 to 2008, but then stabilized or decreased. Conclusions: The increases in breast MRI use observed in the current study have indicated improvements in concordance with breast imaging guidelines. However, women with BRCA mutations remain underscreened, particularly younger women, thereby identifying a clear gap with which to enhance access. Abstract : The use of breast magnetic resonance imaging (MRI) in clinical care in the United States is improving in concordance with breast imaging guidelines. However, women with BRCA mutations remain underscreened with breast MRI, particularly younger women. This finding identifies a clear gap with which to enhance access and mitigate barriers.